Salmonella pathogenicity island-14 is a critical virulence factor responsible for systemic infection in chickens caused by Salmonella gallinarum - Hu, Zuo; Ojima, Shinjiro; Zhu, Zhihao; Yu, Xiaoying; Sugiyama, Makoto; Haneda, Takeshi; Okamura, Masashi; Ono, Hisaya K.; Hu, Dong-Liang (Frontiers in Veterinary Science, 2024)
Salmonella enterica serovar Gallinarum (S. Gallinarum) is an important host-specific pathogen that causes fowl typhoid, a severe systemic, septicaemic and fatal infection, in chickens. S. Gallinarum causes high morbidity and mortality in chickens and poses a significant burden and economic losses to the poultry industry in many developing countries. However, the virulence factors and mechanisms of S. Gallinarum induced systemic infection in chickens remain poorly understood. In this study, we constructed a Salmonella pathogenicity island-14 (SPI-14) mutant strain (mSPI-14) of S. Gallinarum and evaluated the pathogenicity of mSPI-14 in chicken systemic infection model. The mSPI-14 exhibited the same level of bacterial growth and morphological characteristics, but significantly reduced resistance to bile acids compared with that of the wild type (WT) strain in vitro. The virulence of mSPI-14 was significantly attenuated in the chicken oral infection model in vivo. Chickens infected with WT showed typical clinical symptoms of fowl typhoid, with all birds succumbing to the infection within 6 to 9 days post inoculation, and substantial increases in bacterial counts and significant pathological changes in the liver and spleen were observed. In contrast, all mSPI-14-infected chickens survived, the bacterial counts in the organs were significantly lower, and no significant pathological changes were observed in the liver and spleen. The expression of interleukin (IL)-1β, IL-12, CXCLi1, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ in the liver of mSPI-14-infected chickens were significantly lower than those in the WT-infected chickens. These results indicate that SPI-14 is a crucial virulence factor in systemic infection of chickens, and avirulent mSPI-14 could be used to develop a new attenuated live vaccine to prevent S. Gallinarum infection in chickens.